2010
DOI: 10.1007/978-3-642-14183-6_12
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Deontic Explosion by Contextually Restricting Aggregation

Abstract: Abstract. In this paper, we present an adaptive logic for deontic conflicts, called P2.1 r , that is based on Goble's logic SDLaPe-a bimodal extension of Goble's logic P that invalidates aggregation for all prima facie obligations. The logic P2.1 r has several advantages with respect to SDLaPe. For consistent sets of obligations it yields the same results as Standard Deontic Logic and for inconsistent sets of obligations, it validates aggregation "as much as possible". It thus leads to a richer consequence set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Ω + • ) and then according to the abnormalities in Ω wper . 33 Permissive norms. In some applications it is useful to have permissive norms as part of the conditional norms in the premise set.…”
Section: Permissions By Defaultmentioning
confidence: 99%
“…Ω + • ) and then according to the abnormalities in Ω wper . 33 Permissive norms. In some applications it is useful to have permissive norms as part of the conditional norms in the premise set.…”
Section: Permissions By Defaultmentioning
confidence: 99%
“…There too, SDL gives rise to explosion in view of formulas of the form OA ∧ O¬A, OA ∧ P¬A, etc. And there too, authors have suggested weakening the logic in order to tolerate normative conflicts; for some examples, see [12,21,25,28,31,32]. A good oversight can be found in [13].…”
Section: Normative Conflictsmentioning
confidence: 99%
“…In a non-monotonic, non-agentive setting, this strategy was adopted in e.g. [18,21,23,29,30]. Another strategy open for accommodating normative conflicts is to weaken the inheritance principle (INHO).…”
Section: Conflict-tolerant Deontic Logicmentioning
confidence: 99%
“…For some other adaptive deontic logics that can consistently accommodate instances of normative conflicts, see [7,29,39,41]. For an introduction to the framework of adaptive logics, see [3].…”
Section: Adaptive Deontic Logicmentioning
confidence: 99%
See 1 more Smart Citation